Efficacy of Different Drugs Used in COVID Patients in Bangladesh (IAHS Medical Journal, 2022)
Background: COVID 19 era is continuing globally even one and half years of turning out and claiming lives and startled with newly emerged variants. Many studies regarding COVID 19 treatment were published but some options were beneficiary in early stage and later were contradictory to apply it, making clinicians to dim. So this study was carried out reveal potential efficacy of commonly prescribed regimen in COVID unit.Materials and methods: This observational study conducted in three dedicated COVID hospital in Chattogram, Bangladesh. Total 209 cases with RT-PCR positive and symptomatic cases with RT-PCR negative subjects were enrolled in this study.Results: Half of the patients 53% (n=111) who got antiviral remdisivir, 53.6% n=103 were improved, 46.7% n=7 was died and p value < 0.01,comparing to 28.2% (n=59) got favipiravir in whom, 27.6% n=53 were improved, 40% n=6 was died. 16.3% (n=34) patient got Tocilizumab, in whom 73.52% n=25 were improved, 23.52% n=8 was died. 8.6% (n=18) got convalescent plasma in whom 6.3% n=12 was improved, 40% n=6 was died and p value was significant. Those who were given both Tocilizumab and Remdisivir, 76.9% n=20 were improved and 19.2% n=5 were died in comparison to patient treated with Remdisivir only 97.6% n=83 were improved and 2.3% n-2 were died.Conclusion: Even after 18 months of starting COVID, only established treatment options are oxygen and dexamethasone. As data about efficacy of antiviral and others are so changing according to COVID variants and different country. So emphasize should be about prevention and avoiding injudicious use of anti COVID medications.IAHS Medical Journal Vol 5(1), June 2022; 56-59